A new Nearctic species of Atrichopogon (Meleohelea) and a redescription of Atrichopogon (M.) chilensis Ingram & Macfie (Diptera: Ceratopogonidae) - Tóthová, Andrea; Marino, Pablo I. (Zootaxa, 2009)
A new species of Ceratopogonidae from Canada, Atrichopogon (Meloehelea) ladislavi Tóthová, is described. The Patagonian species Atrichopogon (M.) chilensis Ingram & Macfie is restored from synonymy, its female is redescribed and the male is described for the first time.